KAJIAN EMPIRIS FAKTOR-FAKTOR YANG MEMENGARUHI KUALITAS AUDIT - Anindita Astri Khairunisa; Rahmawati Hanny Yustrianthe (Jurnal Ilmiah Wahana Akuntansi, 2015)
In this study that examined the factors that influence the Audit Quality in manufacturing firms 2010-2012. Independent variable is the size of the tenure audit and firm reputation. The purpose of this study is to analyze and demonstrate empirically the effect of tenure audi and firm reputation partially or simultaneously. The population in this research that companies listed in Indonesia Stock Exchange 2010-2012 period, a total of 34 manufacturing companies were taken by using purposive sampling. This data using secondary data with the method of data using logistic regression analysis. This research is expected to provide enter the public accounting firm that provides audit quality. And can be taken into consideration in making a firm decision to maximize firm value or wealth for shareholders. The results of this study indicate that the Audit tenure effect on audit quality. Public accounting firm's reputation effect on audit quality. The results of this test also suggested that both factors simultaneously affect the Audit Quality. Based on the adjusted R2 value of 13.6% indicates that only13.6% of audit quality variable described by audit tenure and reputation of the firm. While the remaining 86.4% is explained by other variables not examined in this study. Keywords: Tenure audit, firm reputation, audit quality